PAYUNG HUKUM TERHADAPASAS KEADILAN UPAH TENAGA KERJA GURU HONORER - Claudia Yosal; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2022)
In paying a wage to a worker, it is common for a company to take note of some of the factors af ectingthe payroll system. Some include qualifications, work locations, the size of the company, industry, andthe entire package of compensation. But what if the pay system does not meet a good gift system that matches the qualifications and labor of an employee, meets the standard of labor, and has a justquality. But the reality is that many employees who get no justice in the wages are not even delayed. Aterrible number of cases of honorer labor, one of whom often fell short of his rights in a fair way. It istherefore evident that such an unfavorable system of wages can have significant economic and socialadverse ef ects. And therefore a new mercenary system established by government regulation (pp) of 36years 2021 on employment according to labor # 13 in 2003 on employment and of working minimumwage change (ump) would not necessarily be able to realize a viable delivery system. So it is importantto formulate solutions and governments should also be able to guarantee regulatory certainty betweencentral and local rules, law enforcement, and economic openness in order to support disruptiveeconomic recovery. In order to provide legal protection from worthy assassins. This study has been thecrucial factor in the change or design of a legal system to replace a viable pay system for an honoraryteacher. Existing regulations are believed to enable the government to respond quickly and address theproblem and its high expectations to avoid minimizing a legal system and its regulations so that theexisting strategies can be implemented to provide legal protection and achieve clear goals.